2020
DOI: 10.1080/25785826.2020.1809951
|View full text |Cite
|
Sign up to set email alerts
|

Harmful and beneficial effects of inflammatory response on reproduction: sterile and pathogen-associated inflammation

Abstract: In reproduction, inflammatory processes play important roles in the development of many pregnancy complications such as preterm labor/birth, recurrent pregnancy loss, recurrent implantation failure, and preeclampsia. Inflammation can be initiated by both microbial and non-microbial causes. Bacterial infection in the feto-maternal interface and uterus can provoke preterm labor/birth, miscarriage, and chronic endometritis. By contrast, inflammation without infection, or 'sterile inflammation,' can also lead to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 258 publications
(312 reference statements)
0
25
0
1
Order By: Relevance
“…The release of key mediators during the activation and degranulation of MCs, including COVID-19-related MC activation, may significantly affect the course of many physiological and pathological reproductive processes in the human body, primarily influencing the permeability of vessels and vascular tone and indirectly modulating electrolyte and water balance or contents of the extracellular matrix [ 12 , 13 ]. Interestingly, the majority of the key physiological processes in the female reproductive tract, including menstruation, follicle development, ovulation, implantation, pregnancy, labor, and postpartum remodeling, consist of a readily visible inflammatory background [ 14 ]. Research successively provides new data.…”
Section: Mcs and Mc-derived Mediators In A Woman's Reproductive Syste...mentioning
confidence: 99%
“…The release of key mediators during the activation and degranulation of MCs, including COVID-19-related MC activation, may significantly affect the course of many physiological and pathological reproductive processes in the human body, primarily influencing the permeability of vessels and vascular tone and indirectly modulating electrolyte and water balance or contents of the extracellular matrix [ 12 , 13 ]. Interestingly, the majority of the key physiological processes in the female reproductive tract, including menstruation, follicle development, ovulation, implantation, pregnancy, labor, and postpartum remodeling, consist of a readily visible inflammatory background [ 14 ]. Research successively provides new data.…”
Section: Mcs and Mc-derived Mediators In A Woman's Reproductive Syste...mentioning
confidence: 99%
“…Many studies have investigated the association of recurrent pregnancy loss (RPL) with immune dysfunction and inflammatory imbalance. Chronic inflammatory response may play an important role in the pathogenesis of miscarriage and implantation failure [ 90 ]. Many studies have reported high level of pro-inflammatory cytokines and chemokines, such as IL-6 [ 91 ], IL-8 [ 92 ], IL-10 [ 93 ], IL-18 [ 94 ], and TNF-α [ 95 ], in blood and decidua of women with RPL.…”
Section: Inflammaging As a Cumulative Effect Of Inflammation And Aging On Fertility And Pregnancy Outcomesmentioning
confidence: 99%
“…Chronic inflammation triggers Th1 polarization of immune cells and downregulation of Th2 response weakening the maternal immune tolerance to embryo implantation and increasing the risk of miscarriage [ 96 ]. Impaired regulatory T cells (Treg) function, together with low prevalence of natural killer (NK) and dendritic cells (DC) have been widely observed in the decidua of women with RPL [ 90 , 97 ]. As a result of innate immune dysfunction, chronic senescent cells accumulate in the decidua leading to SASP response has deleterious effects on implantation [ 84 ].…”
Section: Inflammaging As a Cumulative Effect Of Inflammation And Aging On Fertility And Pregnancy Outcomesmentioning
confidence: 99%
“…Sterile inflammation is classified as inflammation in the absence of infection; immune cells and their signaling molecules are responsible for this inflammation and can impact the onset of preterm labor or birth. Important endogenous molecules such as alarmins (HMGB1, HSP) released by damaged cells and PRRs induce sterile inflammation and may play important roles in the development of innate immunity during early life (24). The nature of the immune stimulation and the timing, severity, and duration of TLR activation will determine the response to infection and the long-term outcomes.…”
Section: Neonatal Pathogenic and Sterile Inflammationmentioning
confidence: 99%